PENGARUH BEBAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA PERAWAT MELALUI BURNOUT SEBAGAI VARIABEL INTERVENING PADA PT. NUSANTARA MEDIKA UTAMA RUMAH SAKIT PERKEBUNAN (JEMBER KLINIK) - Kusumaningrum, Indah Yulia; Sunardi, Sunardi; Saleh, Chairul (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract : This research aims to understand the influence of workload and characteristic of individuals against the performance of the nurse throught burnout in PT. Nusantara Medika Utama Rumah Sakit Perkebunan (Jember Clinic). This research using primary data obtained from the answers of the respondents over kuisioner used in research . The method of analysis the data used in this research was analysis a track ( path analysis ). The method of sampling using census. Population in this research were nures permanent part in -patient service with 57 people. The result of this research is workload and characteristics of individual have positive significant effect on burnout and performance nurse and burnout have negative significant effect on performance of nurse PT. Nusantara Medika Utama Rumah Sakit (Jember Klinik).Keywords: Workload, Characteristic of inidviduals, Performance, Burnout